Club-in-the-Club: Reform under Unanimity - Erik Berglöf; Mike Burkart; Guido Friebel; Elena Paltseva (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
In many organizations, decisions are taken by unanimity giving each member veto power. We analyze a model of an organization in which members with heterogenous productivity privately contribute to a common good. Under unanimity, the least efficient member imposes her preferred effort choice on the entire organization. In the presence of externalities and an incomplete charter, the threat of forming an inner organization can undermine the veto power of the less efficient members and coerce them to exert more effort. We also identify the conditions under which the threat of forming an inner organization is executed. Finally, we show that majority rules effectively prevent the emergence of inner organizations.
Keywords: D2; D7; P4; 330; organizations; club good; voting rules; EU integration; Clubtheorie; Abstimmungsregel; Organisationstheorie; Neue politische Ökonomie; Europäische Integration; Theorie; EU-Staaten